2021
DOI: 10.26508/lsa.202000886
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection induces protective immunity and limits transmission in Syrian hamsters

Abstract: A critical question in understanding the immunity to SARS-COV-2 is whether recovered patients are protected against re-challenge and transmission upon second exposure. We developed a Syrian hamster model in which intranasal inoculation of just 100 TCID50 virus caused viral pneumonia. Aged hamsters developed more severe disease and even succumbed to SARS-CoV-2 infection, representing the first lethal model using genetically unmodified laboratory animals. After initial viral clearance, the hamsters were re-chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 22 publications
11
79
0
Order By: Relevance
“…In the Syrian hamster model, homologous challenge resulted in reduced virus shedding and reduced replication in the lungs [34,35]. In addition, homologous rechallenged hamsters were unable to transmit to naïve animals [35]. Our reinfection data confirm the prior observations and also show that heterologous reinfection with VOC B.1.351 results in limited replication in the lungs, absence of pathology and prevention of onwards transmission in a direct contact transmission model.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the Syrian hamster model, homologous challenge resulted in reduced virus shedding and reduced replication in the lungs [34,35]. In addition, homologous rechallenged hamsters were unable to transmit to naïve animals [35]. Our reinfection data confirm the prior observations and also show that heterologous reinfection with VOC B.1.351 results in limited replication in the lungs, absence of pathology and prevention of onwards transmission in a direct contact transmission model.…”
Section: Discussionsupporting
confidence: 85%
“…The degree of protective immunity by previous SARS-CoV-2 infection in humans is currently unknown, but several reports suggest that reinfection does occasionally occur [31][32][33]. In the Syrian hamster model, homologous challenge resulted in reduced virus shedding and reduced replication in the lungs [34,35]. In addition, homologous rechallenged hamsters were unable to transmit to naïve animals [35].…”
Section: Discussionmentioning
confidence: 99%
“…The infection of other animal models with SARS-CoV-2, including of hamsters, ferrets, and non-human primates, results in mild clinical disease, with a lethal infection only observed in aged hamsters (Selvaraj et al, 2021). The infection of hamsters and ferrets with SARS-CoV-2 does not result in an IFN-b response (Bessie `re et al, 2021;Blanco-Melo et al, 2020;Hoagland et al, 2021), although ISG15 expression was observed after infection and remained elevated to 8 dpi, by which time the virus had already fully cleared (Hoagland et al, 2021).…”
Section: Sars-cov-2 Induction Of Ifn Pathways In Vitromentioning
confidence: 99%
“…Prior exposure of hamsters to SARS-CoV-2 resulted in protection from re-infection, with significantly reduced virus replication in the upper respiratory tract [ 106 ]. Virus was not transmitted to naive contact animals, suggesting that natural immunity to SARS-CoV-2 can prevent transmission.…”
Section: Experimental Sars-cov-2 Transmission Studies: Hamstersmentioning
confidence: 99%